Cardiovascular Effects of Tricyclic Antidepressants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Twenty-four pediatric studies, published from various centers between 1967 and 1996, involving 730 children and adolescents treated with imipramine, amitryptiline, desipramine, or nortryptiline, were surveyed for cardiovascular side effects at the Massachusetts General Hospital, Boston, MA.